Aplicabilidade da NBR ISO 37.120/2017: um estudo de caso no município de Vitória - Es - Salzani, Livia Campos (2019)
With the advent of the large and often unbridled growth of cities (which now house more than 55% of the world's population), urban planners in many countries have turned to trying to solve the problems caused by this phenomenon. At the end of the 1980s, sustainability became a topic of discussion within academia, also gaining space in the media. Over time, ways of creating and assessing the sustainability of the built environment have been developed, and sustainability in urban space has become a new target for research. As research advanced, which sought to assess and compare sustainability in cities, indicators were created, which also function as available tools for the use of public power in their urban planning projects. In 2014, ISO created the international standard ISO 37.120 Sustainable development of communities - Indicators for city services and quality of life, which contain 100 indicators for the creation of sustainable communities. The Brazilian Association of Technical Standards (ABNT) translated and adopted this Standard, making it the NBR ISO 37.120/2017 Sustainable Community Development - Indicators for urban services and quality of life. The premise of the International Standard is that it could be applied in any country, but there were doubts as to the effectiveness of its application in Brazilian cities. This research analyzed the applicability of the evaluation by the indicators in a Brazilian capital - in this case, the municipality of Vitoria, in Espirito Santo. To this end, the existing research methodology in the Standard and the suggestions of search sources were followed. In addition, it used the Access to Information Act to obtain information that exists in public and private agencies, but is not available online. A search for benchmarks was also performed for outcome evaluation, examining indicators in common with those already existing in urban sustainability assessment tools that use scoring parameters. The research concluded that the Standard is applicable to Brazil, however, needs to be adjusted in some of its indicators for the national context. The benchmarks found were not sufficient to evaluate all indicators of the Standard and should be a future investigation.